FRI0424 Comparative analysis of clinically affected and unaffected skin biopsies from scleroderma patients based on rna-sequencing. (12th June 2018) - Makowska, Z.; Buttgereit, A.; Babaei, S.; Limaye, N.; Galant, C.; Houssiau, F.; Weiss, B.; Lesche, R.; McDonald, F.; Lauwerys, B.
Abstract : Background: Systemic sclerosis (SSc) is a complex chronic autoimmune disease characterised by vasculopathy, inflammation and fibrosis across different organ systems. The origin and pathogenesis of the disease are not well understood and symptoms may vary among affected individuals, complicating the diagnosis and therapy. Objectives: We aimed at characterising gene expression profiles in biopsies from affected and unaffected skin of SSc patients. Methods: RNA isolated from affected and unaffected skin biopsies of 23 SSc patients was analysed using polyA-selected RNA sequencing. Paired differential expression analysis was performed with DESeq2, and Molecular Signatures Database gene set collections were used for functional annotation. Results: Paired analysis of SSc gene expression profiles identified over 900 genes differentially regulated between the affected and unaffected skin biopsy samples (adjusted p value<0.05). Macroscopically unaffected skin samples showed clear gene expression differences from the affected skin samples, even though the histological examination showed that pathological changes were already present in most of the samples classified as unaffected. Clustering of differentially expressed genes and subsequent functional characterisation of the resulting gene modules revealed sets of co-expressed genes involved in inflammatory response, extracellular matrix interaction, metabolic function and epithelial differentiation, and highlighted the importance of a number of transcription drivers, such as serum response factor (SRF) or interferon regulatory factor 7 (IRF7). Several genes from the HOX family of transcription factors were found to be among the most significantly differentially expressed genes, pointing to an important role of wound healing and regeneration processes in SSc skin lesions. Additionally, we found significant association between expression of several proteasome subunits and the inflammation score obtained by histological assessment of the skin biopsies. Conclusions: RNA sequencing analysis in paired skin biopsy samples revealed coordinated changes in the gene expression between SSc lesions and macroscopically unaffected skin, providing insights into the SSc skin pathogenesis at the molecular level. Acknowledgements: The research leading to these results has received support from the Innovative Medicines Initiative Joint Undertaking under grant agreement n° 115565, resources of which are composed of financial contribution from the European Union's Seventh Framework Programme (FP7/2007–2013) and EFPIA companies' in kind contribution. Disclosure of Interest: None declared